2019
DOI: 10.1128/aac.02528-18
|View full text |Cite
|
Sign up to set email alerts
|

Fate of CMY-2-Encoding Plasmids Introduced into the Human Fecal Microbiota by Exogenous Escherichia coli

Abstract: The gut is a hot spot for transfer of antibiotic resistance genes from ingested exogenous bacteria to the indigenous microbiota. The objective of this study was to determine the fate of two nearly identical blaCMY-2-harboring plasmids introduced into the human fecal microbiota by two Escherichia coli strains isolated from a human and from poultry meat. The chromosome and the CMY-2-encoding plasmid of both strains were labeled with distinct fluorescent markers (mCherry and green fluorescent protein [GFP]), allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…There were still diverse communities present at the end of the 7-d experiment, albeit with a change in the relative abundance of different taxa. The observed rise of Enterobacteriaceae and Bacteroidaceae has been seen in other experiments with gastrointestinal communities (e.g., [71]) and might be explained by the nutrient content of the medium, micromolar oxygen levels, or such in vitro systems favouring faster population growth [72]. In conditions where antibiotics are applied at higher concentrations or affect a greater fraction of extant taxa, we can expect stronger shifts in community composition in response to antibiotic treatment.…”
Section: Plos Biologysupporting
confidence: 66%
“…There were still diverse communities present at the end of the 7-d experiment, albeit with a change in the relative abundance of different taxa. The observed rise of Enterobacteriaceae and Bacteroidaceae has been seen in other experiments with gastrointestinal communities (e.g., [71]) and might be explained by the nutrient content of the medium, micromolar oxygen levels, or such in vitro systems favouring faster population growth [72]. In conditions where antibiotics are applied at higher concentrations or affect a greater fraction of extant taxa, we can expect stronger shifts in community composition in response to antibiotic treatment.…”
Section: Plos Biologysupporting
confidence: 66%
“…The latter aspect is especially relevant for ST457, which has a documented record of association with human disease and its isolates were assigned to defined pathotypes (ExPEC and/or EAEC) in our virulence analysis. Using an in vitro colon simulation system, Anjum et al 62 showed that E. coli isolated from human faeces and poultry meat were able to adapt and transmit their AMR plasmids to other Enterobacteriaceae in the human gut. Nevertheless, a recent study demonstrated that the dissemination of ESBL/pAmpC genes between animals and humans seems to be mediated by specific plasmid types rather than by expansion of successful E. coli clones 9 .…”
Section: Discussionmentioning
confidence: 99%
“…This substantiates the possibilities of horizontal gene transfer of the ESBL genes from food products or the environment to humans where bacterial pathogens can acquire them. Such transmission is favored by plasmids on which the resistance genes are located (Anjum et al, 2019) as is the case for the bla-CTXM−15 and bla TEM−1 genes, which were located on the IncF plasmid ( Table 4). We observed the plasmid IncF [F1:A1:B1] within all four C3 strains, which had the same ST636 and the same pMLST and showed a SNP difference ranging from 4 to 17.…”
Section: Discussionmentioning
confidence: 99%